Polyploidization of Pelargonium × hortorum L. H. Bailey in greenhouse conditions - P. Jadrná; F. Kobza; O. Plavcová (Horticultural Science, 2009)
This study is aimed at induction of polyploidy in the black-leaved cultivar Pelargonium × hortorum L. H. Bailey Black Velvet Scarlet F1 to obtain basic breeding material for creating new black-leaved tetraploid cultivars. The cultivar Gizela F1 was chosen as a control for the experiment. Tetraploidy was induced in seedlings in the cotyledon stage using various concentrations (from 0.1 to 2.5%) of colchicine water solutions; the treatments were repeated daily for 2, 3, 5 or 7 successive days. The first experiment, done in 2005, was very successful; 17.4% of treated Black Velvet Scarlet F1 plants and 23.7% of treated Gizela F1 plants were tetraploid, and other ploidy levels were also found. However, two other replications from 2006 (involving only five best treatments from the first experiment) were much less successful in comparison with the first one.